(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Hume’s construal of causation historically lays out a philosophical puzzle towards realism and anti-realism; in fact, this scholarship deliberately offers a bit of thoughts for causal realism - in virtue of the Old Hume and New Hume debate, as well as its contextual language. Nevertheless, this dialectic is significantly underestimated by plenty of counterexamples such as empiricism, liberty and necessity, the immateriality of the soul, and copy principle. In response to these brainstorming facets, this research article intends to determine that Hume is a causal anti-realist; I have, in turn, explored three supporting arguments to defend the compelling idea: conventional manifestation of causality - Hume’s advocacy of necessary connection - the idea of liberty and necessity. However, this critical study is restricted to examine other substantial reflections on those which are included in the compositions of Treatise and Enquiry.